Institutional capacity in Honduras is strengthened to address climate change and variability challenges by using CCAFS-CIAT science. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Following the Climate Change Law (2013), the Secretariat of Agriculture and Livestock (SAG) has positioned itself as a leader on climate action and increased its capacity to address climate change and variability thanks to CCAFS support. Today, Honduras has robust policies and instruments to address climate issues in the agri-food sector, informed by science such as the Climate Change Adaptation Strategy (2015-2025), the Institutional Plan for Climate Change Adaptation (2019-2023), seven Local Technical Agroclimatic Committees (LTACs), and municipal adaptation plans.